Penyalahgunaan Kekuasaan dan Viktimisasi Proyek Strategis Nasional di Pulau Rempang - Jayusman, Dandi; Shakhila, Annarentika Faajra; Pena, Benedikta Wewieta Li; Saskia, Elly; Rantung, Esterlita Nova Yaser; Febriyanti, Heni Nur; Pramesti, Athifah Danika (UI Scholars Hub, 2025)
Implementing the National Strategic Project (PSN) on Rempang Island caused controversy over the abuse of power that harmed some local communities. This research aims to analyze the conception of victims of abuse of power in the implementation of PSN, the structural victimization of PSN, the impact of PSN victimization, and the regulation of the rights of people affected by PSN. The research method used is doctrinal research with statutory regulations, victimology, and case approaches. The study shows that communities who experienced repression and violence during the implementation of PSN on Rempang Island are victims of abuse of power. Structural victimization in the implementation of PSN was caused by the dominance and imbalance of power between the government and communities, which led to re-victimization (secondary victimization). PSN victimization had financial, psychological, physical, social, and political participation impacts on some communities on Rempang Island. Unfortunately, the PSN legal framework only regulates compensation for communities affected by land acquisition for PSN. There are no specific rules to provide counseling, assistance, and material, medical, psychological, and social support to the affected communities. The legal gap regarding the rights of the affected communities by PSN obstructed the recovery of losses experienced by some communities on Rempang Island.